2020
DOI: 10.1088/1757-899x/949/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

CollectionCare: an affordable service for the preventive conservation monitoring of single cultural artefacts during display, storage, handling and transport

Abstract: In recent years there has been growing interest in the development of devices and software packages that allow museum decision-makers to manage the environmental conditions in collections and estimate the evolution of degradation of objects. A system able to monitor the environmental conditions but also to provide warnings and recommendations about failure boundaries would optimize conservation actions and strategies thus ensuring proper conservation of the collections in the long term. Collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Other authors [ 43 ] have reported similar results using wireless sensors in cultural heritage because the data sent by some nodes to the gateway reached 100% while this percentage was lower in others (75–93%). The experience with this deployment and the evolution of radio technology has allowed us to redesign the node for better behavior in historic buildings and lower communication loss due to collisions [ 62 ], e.g., our deployment in Alava’s Arms Museum achieves DER higher than 95%.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors [ 43 ] have reported similar results using wireless sensors in cultural heritage because the data sent by some nodes to the gateway reached 100% while this percentage was lower in others (75–93%). The experience with this deployment and the evolution of radio technology has allowed us to redesign the node for better behavior in historic buildings and lower communication loss due to collisions [ 62 ], e.g., our deployment in Alava’s Arms Museum achieves DER higher than 95%.…”
Section: Resultsmentioning
confidence: 99%
“…The projections of observations (hours, in this case) over these directions maximising data variability are called scores. In contrast, the contributions of variables in the formation of a given component are called loadings, with p [1] being the loadings in the formation of the first principal component (PC1); p [2] , the loadings of PC2; and so on. The scatterplot of the loadings corresponding to PC1 and PC2, which is commonly referred to as PC1/PC2 loading plot, was inspected visually, because it usually summarises the most relevant information from the data series.…”
Section: Multivariate Statistical Methodsmentioning
confidence: 99%
“…The analysis of microclimate data has become an increasingly common practice to pinpoint the agents causing the deterioration of artworks. In this context, one of the objectives of the European project CollectionCare (www.collectioncare.eu (accessed on 1 April 2022) [1]) is the continuous monitoring of the environmental conditions (e.g., temperature, relative humidity, light, and air pollutants) to which an individual artwork is exposed during exhibition, storage, handling, or transport.…”
Section: Introductionmentioning
confidence: 99%
“…A.S.J.S. gratefully acknowledges the support of the European Union's Horizon 2020 research and innovation programme CollectionCare (Perles et al, 2020), under grant agreement N. 814624. J.J.H.…”
Section: Acknowledgementsmentioning
confidence: 99%